Penerapan Metode Wafa dalam Meningkatkan Kefasihan Membaca Al-Qur’an Peserta Didik di SDIT Al-Adzkia Sentul Jombang - Ahmad Nizar Alam; Chusnul Chotimah; Emi Lilawati (Lembaga Yasin AlSys, 2026)
Differences in students’ initial abilities to recognize hijaiyah letters, articulate the correct points of pronunciation, apply tajwid rules and proper vowel lengths, and read fluently and accurately pose challenges in Qur’an learning. This study aimed to describe the implementation of the Wafa method in improving students’ Qur’an reading fluency at SDIT Al-Adzkia Sentul, Jombang, and to identify the factors supporting and inhibiting its implementation. The study employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation and were then analyzed through data reduction, data presentation, and conclusion drawing. The findings showed that the Wafa method was implemented systematically through a right-brain approach, the use of the Hijaz melody, talaqqi, demonstration, repeated practice (drills), multisensory learning, and periodic evaluation. The implementation of this method supported improvements in Qur’an reading fluency, particularly in the accuracy of articulation points, application of tajwid rules, reading fluency, and students’ self-confidence. Its successful implementation was supported by teacher competence, the availability of learning media, school support, and students’ enthusiasm. The inhibiting factors included differences in initial ability, limited instructional time, and insufficient practice at home. This study concludes that the Wafa method can serve as a systematic, engaging, and adaptive alternative for Qur’an learning that meets students’ needs. These findings provide practical implications for schools and teachers in designing instruction that supports continuous improvement in Qur’an reading fluency.